2000
DOI: 10.1128/jb.182.17.4899-4905.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Candida albicans P1-Type ATPase in Resistance to Copper and Silver Ion Toxicity

Abstract: Copper ion homeostasis is complicated in that copper is an essential element needed for a variety of cellular processes but is toxic at excess levels. To identify Candida albicans genes that are involved in resistance to copper ion toxicity, a library containing inserts of C. albicans genomic DNA was used to complement the copper sensitivity phenotype of a Saccharomyces cerevisiae cup1⌬ strain that is unable to produce Cup1p, a metallothionein (MT) responsible for high-level copper ion resistance. A P1-type AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 56 publications
(63 reference statements)
3
110
0
1
Order By: Relevance
“…The E. coli homologue of this type of ATPase, copA, was shown to pump Cu(I) out of cells (Rensing et al, 2000). It was reported that overexpression of the CRD1 gene conferred copper-resistance on S. cerevisiae cells (Riggle and Kumamoto, 2000;Weissman et al, 2000). In S. cerevisiae, there is a structurally similar P-type ATPase encoded by PCA1 (Rad et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The E. coli homologue of this type of ATPase, copA, was shown to pump Cu(I) out of cells (Rensing et al, 2000). It was reported that overexpression of the CRD1 gene conferred copper-resistance on S. cerevisiae cells (Riggle and Kumamoto, 2000;Weissman et al, 2000). In S. cerevisiae, there is a structurally similar P-type ATPase encoded by PCA1 (Rad et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of yeast have different mechanisms for developing copper-resistance. In Candida albicans, a P-type ATPase encoded by the CRD1 gene plays a major role in copper-resistance: excessive copper in the cytoplasm is exported from the cells by this enzyme (Riggle and Kumamoto, 2000;Weissman et al, 2000). The E. coli homologue of this type of ATPase, copA, was shown to pump Cu(I) out of cells (Rensing et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans strains are listed in Table 1. Parent strains were CAI4 (⌬ura3/⌬ura3) (17) and CAPR306 (⌬ura3/⌬ura3 ⌬crd1/⌬crd1) (42). The crd1 deletion strain CAPR306 was used as a parent in these studies because the crd1 mutation provides a convenient genetic marker for experiments such as protoplast fusion.…”
Section: Methodsmentioning
confidence: 99%
“…A subtractive library enriched by T. rubrum genes expressed in the presence of cytotoxic components showed the upregulation of a gene encoding copper-resistanceassociated P-type ATPase after fluconazole contact (Paião et al, 2007). Copper is an essential metabolic element as a cofactor of many cellular enzymes, and copper-transporting P-type ATPases are found in eukaryotic organisms and require an iron transporter for adaptation in different environments and hosts (Riggle & Kumamoto, 2000). The absence of normal copper-transporter activity in Cryptococcus neoformans after VPH1 gene deletion was observed in an avirulent mutant interfering in laccase activity (Zhu & Williamson, 2003), a strong virulence factor in this opportunistic pathogen.…”
Section: Transporter Proteins In T Rubrum Pathogenesismentioning
confidence: 99%